2005
DOI: 10.1002/pds.1051
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological investigation of off‐label anticonvulsant drug use in the Georgia Medicaid population

Abstract: The anticonvulsant off-label use in the Georgia Medicaid population is very high (71%). Only a modest proportion of these off-label uses are supported by evidence from controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…In a more recent survey of prescriptions by 113 primary care physicians in Quebec, Canada, the prevalence of off-label use by indication was highest for CNS drugs (26.3 %) and, among the latter, AEDs ranked first with a 66.6 % rate [10]. Likewise, among 48,648 patients prescribed AEDs in the Georgia Medicaid database, off-label use by indication or age was identified in 71.3 % of recipients, with a percentage as high as 86 % for gabapentin users [8]. In another study that focused mainly on off-label use by age, lamotrigine and oxcarbazepine were among the top three drugs prescribed off-label in Italian Child Neurology divisions [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent survey of prescriptions by 113 primary care physicians in Quebec, Canada, the prevalence of off-label use by indication was highest for CNS drugs (26.3 %) and, among the latter, AEDs ranked first with a 66.6 % rate [10]. Likewise, among 48,648 patients prescribed AEDs in the Georgia Medicaid database, off-label use by indication or age was identified in 71.3 % of recipients, with a percentage as high as 86 % for gabapentin users [8]. In another study that focused mainly on off-label use by age, lamotrigine and oxcarbazepine were among the top three drugs prescribed off-label in Italian Child Neurology divisions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys of off-label prescribing of AEDs have mostly addressed their use for indications outside epilepsy [8][9][10][11], and no comprehensive study seems to have systematically evaluated the modalities and predictors of off-label prescribing in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Zito et al (2006) found that anticonvulsants were given to children with psychiatric diagnoses without seizures (81%), children with a diagnosis of seizures (19%), and children with seizures and psychiatric diagnoses (71%) [3]. An epidemiological study of the off-label use of anticonvulsants has also been carried out by Chen et al (2005) in the Medicaid population of the U. S. state of Georgia. The results showed an off-label use of anticonvulsant of as much as 71.3% with gabapentin as the most widely prescribed off-label anticonvulsant (86%).…”
Section: Methodsmentioning
confidence: 99%
“…Four comorbidities of patients receiving off-label anticonvulsants are patients with diabetes mellitus, depression, schizophrenia, and pain. Neurologists were found to be the practitioners who most prescribe off-label anticonvulsants [4].…”
Section: Methodsmentioning
confidence: 99%
“…However, the changing landscape of maternal exposures makes continued clinical, surveillance, and research vigilance necessary. For example, new medications enter the market every year, the vast majority of which have insufficient clinical or epidemiological data to determine teratogenic risk [99, 100]; in addition, existing medications may be approved for new indications or used off label for a wider range of conditions [101]. Further, although the prevalence of traditional smoking has decreased over time, the introduction and increasing use of the e-cigarette may increase the exposure to nicotine during pregnancy [102].…”
Section: Challenges In Translationmentioning
confidence: 99%